The Use and Reception of Varieties of Spanish in Videogames - Zorrakin-Goikoetxea, Itziar (Journal of Audiovisual Translation, 2022)
With more than 585 million speakers, Spanish promises to be a profitable target language for videogame sales. However, as Spanish has such a wide geographical distribution, the question of varieties deserves some attention. Companies and websites alike have recently started to differentiate between European Spanish and Latin American Spanish. This paper presents a three-phase study to delve into the matter. Based on a catalogue of 3003 videogames available on Steam in Spanish and published between 2006 and 2016, a survey among 172 developers is carried out to confirm the companies’ preferred varieties. Then, the analysis of a small corpus extracted from the catalogue shows whether in‑game text actually represents the chosen variety of Spanish. Finally, a survey among 569 gamers provides some insight into their tolerance for foreign varieties. This paper aims to describe the current situation and provide a starting point for further reflection on some of the questions posed by the results of this study. Lay summary Videogame localisation is the process of adapting a videogame from one market to another. This includes the translation of the script and sometimes the adaptation of images and other aspects. Because Spanish is one of the most spoken languages in the world, localising a game into Spanish can often be profitable, but different countries speak different forms of Spanish. Each form of Spanish is called a variety. This article is divided in three parts. First, we have created a catalogue from the games published in a video game website (Steam) in Spanish between 2006 and 2016. Then we have asked the developers of the games to confirm which variety of Spanish they wanted to use. Second, we have analysed some of these games to check if the variety of Spanish used in the games is the variety the developers wanted. Finally, we have asked 569 gamers if they care about the variety of Spanish used in videogames. The objective of this article is to describe the current situation. This way we will start to understand whether the chosen variety of Spanish is represented in games, and whether the variety of Spanish is important for gamers. The final objective of the research is to help the developers to choose the best option for their game.